Hedging policies to reduce agency costs in Brazil - Vinícius Medeiros Magnani; Marcelo Augusto Ambrozini; Rafael Moreira Antônio; Rafael Confetti Gatsios (Journal of Risk and Financial Management, 2022)
Given the recent Brazilian economic scenario, characterized by political uncertainties and economic instabilities, it is essential for companies to engage in hedging as part of their financial policy in order to prevent their results from being affected by market frictions. In this context, the present study aimed to verify the impact of hedging on the agency costs of Brazilian companies. The methodology used was that of panel data contemplating a manually collected database of 154 companies between 2010 and 2017 (all companies that use derivatives for hedging). The results obtained agree with the literature on hedging and agency costs, indicating that the greater the use of hedging, the lower the agency costs faced by shareholders, expanding on the discussions involving developed markets. This relationship shows that by using hedging in a company's financial policy, managers can minimize the impacts of market frictions and reduce the residual losses of shareholders in relation to what would otherwise occur.
Keywords: 650; agency costs; corporate finance; hedging; market friction